THE IMPACT OF SOCIAL SPACES IN RESIDENTIAL NEIGHBOURHOOD DURING THE COVID-19 PANDEMIC: URBAN FARMING INTO A SELF-SUFFICIENT COMMUNITY - Chua Siu Ting; Hussein, Hazreena (Journal of Surveying, Construction and Property, 2025)
The announcement of Malaysia’s first coronavirus (COVID-19) case in January 2020 triggered a nationwide lockdown on March 18, significantly affecting food supply chains and exposing the weaknesses of non-self-sufficient economies. This study critically explores residents’ perceptions of social spaces in Port Dickson, Negeri Sembilan during the pandemic through a mixed-method approach. It combines photographic documentation and a questionnaire survey to assess the impact on residents’ quality of life. Insights from a semi-structured interview with representatives of PLAN Malaysia in Negeri Sembilan, revealed that the design of social spaces is intended to enhance cost efficiency while alleviating the burden on local authorities. Results indicated that majority of the respondents experienced significant stress during the pandemic, driven by anxiety, job loss, and livelihood challenges while many emphasized the importance of effective space allocation and varied options within residential neighborhoods. These findings imply that strategically designed social spaces and zoning practices are key to developing self-sufficient communities in residential areas. Future research agenda should prioritize on the long-term implications of diverse social space designs for community well-being and self-sufficiency in the post-pandemic landscape.